A purification process for high-purity quartz sand
Patent Information
- Application Number
- CN202511513584.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-22
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-10-22
AI Technical Summary
此外,随着绿色环保成为工业生产的重要发展方向,酸和碱的使用不仅对环境具有潜在危害,还会增加酸碱处理成本
本发明以石英矿为原料,首先将石英与氯盐混合后进行煅烧,煅烧过程中石英发生晶型转变,体积增大,同时晶体中的杂质成分转化为气态或凝聚态的氯化物,从而实现组分的分离或富集,达到深度提纯的效果。随后进行水淬处理,水淬时晶体体积突然缩小,晶体缺陷处的内应力迅速增大,促使晶体在缺陷处破裂,使原石英中的包裹体和裂隙中的杂质暴露在颗粒表面,便于后续除杂。接着在微波辅助下,通过改性捕收剂对石英进行浮选。在微波场的作用下,石英砂表面的晶格结构会发生一定程度的振动和调整,使得石英砂和杂质矿物在浮选过程中的可浮性差异增大。同时,捕收剂的分子活性增强,促进药剂与石英砂表面以及杂质矿物表面的化学反应,从而提高石英砂的纯度。最后进行酸浸和烘干处理,制得高纯度多功能石英砂。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of quartz sand technology, specifically a purification process for high-purity quartz sand. Background Technology
[0002] High-purity quartz sand, due to its excellent physicochemical properties such as high temperature resistance, corrosion resistance, low thermal expansion, high insulation, and high light transmittance, has become an indispensable raw material in fields such as semiconductors, new energy, fiber optic communications, and aerospace. With continuous technological advancements, the demand for high-purity quartz sand from high-tech industries continues to grow, and the quality requirements are correspondingly increasing. However, currently, my country mainly relies on imports for high-purity quartz sand, and domestic production falls far short of domestic market demand. This situation is mainly due to two reasons: firstly, the quality of raw quartz ore in my country is substandard; no suitable quartz deposits for preparing high-purity quartz sand have been discovered, or the raw ore detection technology is imperfect, making it impossible to accurately assess the purification potential of the raw ore; secondly, my country's high-purity quartz sand preparation technology is substandard, making it impossible to purify raw quartz ore to the required grade, or the widespread use of high-cost processing technologies such as acid washing and chlorination makes industrial-scale mass production difficult.
[0003] Flotation, as one of the most important purification methods in the process of quartz sand refining, can effectively separate quartz from impurities and gangue minerals. Therefore, all high-purity quartz sand preparation processes rely on flotation. The selection of flotation reagents is a key factor affecting flotation efficiency, mainly including collectors, depressants, regulators, and frothers. Furthermore, with green and environmentally friendly practices becoming an important development direction in industrial production, the use of acids and alkalis not only poses potential environmental hazards but also increases acid and alkali treatment costs. Therefore, developing green and environmentally friendly flotation methods has become one of the research hotspots in the field of mineral processing today. Summary of the Invention
[0004] The present invention aims to provide a purification process for high-purity quartz sand to solve the problems existing in the prior art.
[0005] To solve the above-mentioned technical problems, the present invention proposes the following technical solution: a purification process for high-purity quartz sand, specifically including the following steps: (1) Calcination and water quenching: First, clean the quartz ore with deionized water, then crush it into particles of 2-5 mm in a crusher. Next, add 8-14% chloride salt by weight of the quartz ore and mix thoroughly. Place the mixture in a muffle furnace and calcine at 600-1000℃ for 2-6 hours. After calcination, immediately pour the material into distilled water at 16-22℃ for water quenching for 0.1-1 minute. Subsequently, dry it at 100-150℃ for 3-5 hours. Finally, grind and sieve the dried material to obtain quartz sand.
[0006] (2) Microwave flotation: Quartz sand is placed in a flotation tank equipped with a microwave device, deionized water and modified collector are added, and flotation is carried out after stirring evenly. The floating foam is collected, filtered, and the solid is taken and washed three times with deionized water to finally obtain purified quartz sand.
[0007] (3) Acid leaching and drying: Transfer the purified quartz sand to a container, add a mixed acid solution of 5-7 times the weight of the purified quartz sand, and stir at 50 rpm for 2-4 hours. After filtration, take the solid, soak it in sodium carbonate aqueous solution for 20-40 minutes, and then wash it with deionized water. Then dry it at 100-150℃ for 3-5 hours to obtain high-purity quartz sand.
[0008] Furthermore, the chloride salt used in step (1) is selected from any one of sodium chloride, ammonium chloride, and calcium chloride.
[0009] Furthermore, the sieve aperture range used in the sieving process in step (1) is 40 to 220 mesh.
[0010] Further, the modified collector described in step (2) is prepared as follows: 6-12 parts of (2-aminoethyl)trimethylammonium chloride hydrochloride, 8-14 parts of pentaerythritol and 30-50 parts of ethanol are mixed evenly, nitrogen gas is introduced, and 35-65 parts of bisphenol F diglycidyl ether-ethanol solution are added dropwise at a rate of 3 mL / min under stirring conditions of 20-30℃ and 100 rpm. After reacting for 30-40 hours, the temperature is raised to 65-75℃ and the reaction is continued for 25-35 hours. The mixture is then concentrated for 1-2 hours under a vacuum of -0.1 to -0.08 MPa to obtain the modified collector.
[0011] Furthermore, the concentration of bisphenol F diglycidyl ether in the bisphenol F diglycidyl ether-ethanol solution is 20 wt%.
[0012] Furthermore, the flotation conditions in step (2) include: an aeration rate of 0.5~1.5 m³ / min, a microwave frequency of 1250~2150 MHz, a stirring speed of 150~300 r / min, and a flotation time of 3~9 min.
[0013] Furthermore, in step (2), the weight of deionized water is 4 to 8 times the weight of quartz sand, and the weight of modified collector is 0.1 to 1.5% of the weight of quartz sand.
[0014] Furthermore, the mixed acid solution in step (3) is prepared by mixing 6wt% sulfuric acid, 2wt% hydrochloric acid and 10wt% oxalic acid in a volume ratio of 1:2:1.
[0015] Furthermore, the sodium carbonate content of the sodium carbonate aqueous solution in step (3) is 10 wt%.
[0016] Furthermore, in step (3), the pH value of the washing solution after washing is in the range of 6.5 to 7.5.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are: This invention uses quartz ore as raw material. First, quartz is mixed with chloride salts and calcined. During calcination, the quartz undergoes a crystal transformation, increasing in volume. Simultaneously, impurities in the crystals are converted into gaseous or condensed chlorides, achieving component separation or enrichment and deep purification. Next, water quenching is performed. During water quenching, the crystal volume suddenly shrinks, and the internal stress at crystal defects rapidly increases, causing the crystals to fracture at these defects. This exposes inclusions and impurities in the original quartz to the particle surface, facilitating subsequent impurity removal. Then, under microwave assistance, quartz is floated using a modified collector. Under the influence of the microwave field, the lattice structure of the quartz sand surface vibrates and adjusts to a certain extent, increasing the difference in floatability between the quartz sand and impurity minerals during flotation. Simultaneously, the molecular activity of the collector is enhanced, promoting chemical reactions between the reagent and the surfaces of the quartz sand and impurity minerals, thereby improving the purity of the quartz sand. Finally, acid leaching and drying are performed to obtain high-purity, multifunctional quartz sand.
[0018] The modified collector is prepared by copolymerizing (2-aminoethyl)trimethylammonium chloride hydrochloride, bisphenol F diglycidyl ether, and pentaerythritol tetramine to form a three-dimensional network structure. This structure can form multi-site adsorption with the active sites on the quartz surface, reducing the contact area between the quartz surface and water, thereby enhancing the hydrophobicity of the quartz and improving the separation effect. The quaternary ammonium salt structure introduced by (2-aminoethyl)trimethylammonium chloride hydrochloride is adsorbed onto the quartz surface by electrostatic force, causing the hydrophobic groups in the modified collector to face the aqueous phase, further enhancing the hydrophobicity of the quartz sand surface. This property makes it easier for the quartz sand to adhere to the bubbles and float, achieving the separation of quartz from impurity minerals. The multiple rigid benzene rings in bisphenol F diglycidyl ether can prevent water molecules from approaching the quartz surface, greatly improving the hydrophobicity and facilitating better adhesion of quartz to bubbles during flotation. At the same time, this structure can also improve the stability of the collector under microwave conditions, indirectly enhancing its collecting ability. Detailed Implementation
[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0020] To more clearly illustrate the method provided by the present invention, the following embodiments are provided in detail. The testing methods for various indicators of the high-purity quartz sand produced in the following embodiments are as follows: Determination of SiO2 content and impurity element content: Take the same weight of the example and comparative sample, and analyze the content of each element in the quartz sand by inductively coupled plasma atomic emission spectrometry (ICP-OES) according to JC / T2027 standard.
[0021] Example 1: (1) Calcination and water quenching: The quartz ore was washed clean with deionized water, placed in a crusher, and crushed into 2mm particles. 8% sodium chloride by weight of the quartz ore was added and mixed thoroughly. The mixture was placed in a muffle furnace and calcined at 600℃ for 2 hours, then immediately poured into distilled water at 16℃ for 0.1 minutes for water quenching. Finally, it was dried at 100℃ for 3 hours, ground, and sieved through a 40-mesh sieve to obtain quartz sand.
[0022] (2) Preparation of modified collector: 6 parts of (2-aminoethyl)trimethylammonium chloride hydrochloride, 8 parts of pentaerythritol tetramine, and 30 parts of ethanol were mixed thoroughly. Nitrogen gas was introduced, and 35 parts of a 20wt% bisphenol F diglycidyl ether-ethanol solution were added dropwise at a rate of 3 mL / min under stirring at 100 rpm at 20 °C. After reacting for 30 hours, the temperature was raised to 65 °C, and the reaction was continued for 25 hours. Finally, the mixture was concentrated under a vacuum of -0.1 MPa for 1 hour to obtain the modified collector.
[0023] (3) Microwave flotation: Quartz sand was placed in a flotation tank equipped with a microwave device, and deionized water at 4 times the weight of the quartz sand and modified collector at 0.1% of the weight of the quartz sand were added. After stirring evenly, flotation was carried out for 3 minutes under the conditions of an aeration rate of 0.5 m³ / min, a microwave frequency of 1250 MHz, and a stirring speed of 150 r / min. The floating foam was collected, filtered, and the solid was taken and washed 3 times with deionized water to finally obtain purified quartz sand.
[0024] (4) Acid leaching and drying: Transfer the purified quartz sand to a container and add a mixed acid solution five times its weight in water. The volume ratio of the mixed acid solution is 6% sulfuric acid: 2% hydrochloric acid: 10% oxalic acid = 1:2:1. Stir at 50 rpm for 2 hours, filter and collect the solid. Soak in a sodium carbonate aqueous solution with a sodium carbonate content of 10% for 20 minutes, wash with deionized water until the pH of the washing solution is 6.5, and then dry at 100℃ for 3 hours to obtain high-purity quartz sand.
[0025] Example 2: (1) Calcination and water quenching: The quartz ore was washed clean with deionized water and crushed into 3.5 mm particles in a crusher. Then, 11% chloride salt by weight of the quartz ore was added, wherein the mass ratio of sodium chloride, ammonium chloride and calcium chloride was 1:3:0.5. The mixture was placed in a muffle furnace and calcined at 800°C for 4 hours, and immediately poured into distilled water at 19°C for 0.5 minutes for water quenching. Finally, it was dried at 125°C for 4 hours, ground and sieved through a 130-mesh sieve to obtain quartz sand.
[0026] (2) Preparation of modified collector: 9 parts of (2-aminoethyl)trimethylammonium chloride hydrochloride, 11 parts of pentaerythritol tetramine, and 40 parts of ethanol were mixed thoroughly. Nitrogen gas was introduced, and 50 parts of a 20wt% bisphenol F diglycidyl ether-ethanol solution were added dropwise at a rate of 3 mL / min under stirring at 25°C and 100 rpm. After reacting for 35 hours, the temperature was raised to 70°C, and the reaction was continued for another 30 hours. Finally, the mixture was concentrated under a vacuum of -0.09 MPa for 1.5 hours to obtain the modified collector.
[0027] (3) Microwave flotation: Quartz sand was placed in a flotation tank equipped with a microwave device, and deionized water at 6 times the weight of the quartz sand and modified collector at 0.8% of the weight of the quartz sand were added. After stirring evenly, flotation was carried out for 6 minutes under the conditions of an aeration rate of 1.0 m³ / min, a microwave frequency of 1700 MHz, and a stirring speed of 225 r / min. The floating foam was then collected, the solid was filtered, and washed 3 times with deionized water to obtain purified quartz sand.
[0028] (4) Acid leaching and drying: Transfer the purified quartz sand to a container and add a mixed acid solution with a weight of 6 times that of the purified quartz sand. The mixed acid solution is composed of 6 wt% sulfuric acid, 2 wt% hydrochloric acid, and 10 wt% oxalic acid in a volume ratio of 1:2:1. Stir at 50 rpm for 3 hours, and filter to obtain the solid. Then soak in a sodium carbonate aqueous solution with a sodium carbonate content of 10 wt% for 30 minutes, and wash with deionized water until the pH of the washing solution is 7.0. Finally, dry at 125℃ for 4 hours to obtain high-purity quartz sand.
[0029] Example 3: (1) Calcination and water quenching: The quartz ore was washed clean with deionized water, placed in a crusher, and crushed into 5mm particles. Then, 14% of the weight of the quartz ore was added with chloride salt. The mass ratio of sodium chloride, ammonium chloride, and calcium chloride in the chloride salt was 1:2:0.7. The mixture was placed in a muffle furnace and calcined at 1000℃ for 6 hours. Immediately after quenching in distilled water at 22℃ for 1 minute, it was dried at 150℃ for 5 hours. After grinding, it was sieved through a 220-mesh sieve to obtain quartz sand.
[0030] (2) Preparation of modified collector: 12 parts of (2-aminoethyl)trimethylammonium chloride hydrochloride, 14 parts of pentaerythritol, and 50 parts of ethanol were mixed evenly. Under nitrogen purging, 65 parts of a 20 wt% bisphenol F diglycidyl ether-ethanol solution were added dropwise at a rate of 3 mL / min while stirring at 100 rpm at 30 °C. After reacting for 40 hours, the temperature was raised to 75 °C, and the reaction was continued for 35 hours. Finally, the mixture was concentrated under a vacuum of -0.08 MPa for 2 hours to obtain the modified collector.
[0031] (3) Microwave flotation: Quartz sand was placed in a flotation tank equipped with a microwave device, and deionized water at 8 times the weight of the quartz sand and modified collector at 1.5% of the weight of the quartz sand were added. After stirring evenly, flotation was carried out for 9 minutes under the conditions of an aeration rate of 1.5 m³ / min, a microwave frequency of 2150 MHz, and a stirring speed of 300 r / min. Subsequently, the floating foam was collected, the solid was filtered, and washed three times with deionized water to obtain purified quartz sand.
[0032] (4) Acid leaching and drying: Transfer the purified quartz sand to a container and add a mixed acid solution with a weight of 7 times that of the purified quartz sand. The mixed acid solution is composed of 6 wt% sulfuric acid, 2 wt% hydrochloric acid, and 10 wt% oxalic acid in a volume ratio of 1:2:1. Stir at 50 rpm for 4 hours, filter, and collect the solid. Soak in a sodium carbonate aqueous solution with a sodium carbonate content of 10 wt% for 40 minutes, then wash with deionized water until the pH of the washing solution is 7.5. Finally, dry at 150℃ for 5 hours to obtain high-purity quartz sand.
[0033] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that ammonium chloride is not added during calcination, while the other steps are the same as in Example 2.
[0034] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that after calcination, the temperature is lowered to 100°C and then poured into distilled water for water quenching. The remaining steps are the same as in Example 2.
[0035] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that microwaves are not used during flotation, while the other steps are the same as in Example 2.
[0036] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that (2-aminoethyl)trimethylammonium chloride hydrochloride was not added when synthesizing the modified collector, and the remaining steps were the same as in Example 2.
[0037] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that bisphenol F glycidyl ether is not added when synthesizing the modified collector, and the other steps are the same as in Example 2.
[0038] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that pentaerythritol is not added when synthesizing the modified collector, while the other steps are the same as in Example 2.
[0039] Example of effect Table 1 below shows the performance analysis results of the high-purity quartz sand used in Examples 1 to 3 and Comparative Examples 1 to 6 of the present invention.
[0040] Table 1
[0041] Comparing the experimental data of Examples 1, 2, and 3 with Comparative Examples 1 and 2 reveals that the process of first calcining with chloride salts followed by water quenching induces a crystal transformation and volume expansion in quartz during calcination. Simultaneously, impurities in the crystals are converted into gaseous or condensed chlorides, achieving component separation and enrichment, resulting in deep purification. During water quenching, the crystal volume shrinks rapidly, causing a rapid increase in internal stress at crystal defects, leading to crystal fracture. This exposes inclusions and impurities in the original quartz to the particle surface, facilitating subsequent impurity removal. Furthermore, comparing the experimental data of Examples 1, 2, and 3 with Comparative Example 3 shows that under the influence of a microwave field, the lattice structure of the quartz sand surface vibrates and adjusts to a certain extent. This not only increases the difference in floatability between quartz sand and impurity minerals during flotation but also enhances the molecular activity of the collector, promoting chemical reactions between the reagent and the surfaces of both quartz sand and impurity minerals, thereby further improving the purity of the quartz sand. Comparing the experimental data of Examples 1, 2, and 3 with Comparative Examples 4, 5, and 6, it can be found that the modified collector prepared by copolymerization of (2-aminoethyl)trimethylammonium chloride hydrochloride, bisphenol F diglycidyl ether, and pentaerythritol has the following characteristics: First, the collector can form a three-dimensional network structure, forming multi-point adsorption with the active sites on the quartz surface, thereby reducing the contact area between the quartz surface and water and enhancing the hydrophobicity of the quartz. Second, the introduced quaternary ammonium salt structure is adsorbed onto the quartz surface by electrostatic force, causing the hydrophobic groups in the modified collector to face the aqueous phase, further enhancing the hydrophobicity of the quartz sand surface, making it easier to adhere to bubbles and float with them, thus achieving the separation of quartz from impurity minerals. In addition, the multiple rigid benzene rings in the collector can prevent water molecules from approaching the quartz surface, significantly improving the hydrophobicity and allowing the quartz to better adhere to bubbles during flotation. On this basis, the stability of the collector under microwave conditions is also improved, thereby enhancing its collecting ability.
[0042] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.
Claims
1. A purification process for high-purity quartz sand, characterized in that, The following purification processes are included: (1) Calcination and water quenching: Wash the quartz ore with deionized water, place it in a crusher, crush it into particles of 2-5 mm, add 8-14% chloride salt by weight of quartz ore and mix evenly, place it in a muffle furnace and calcine at 600-1000℃ for 2-6 h, immediately pour it into distilled water at 16-22℃ for 0.1-1 min, dry it at 100-150℃ for 3-5 h, grind it and sieve it to obtain quartz sand; (2) Microwave flotation: Quartz sand is placed in a flotation tank equipped with a microwave device, deionized water and modified collector are added, and after stirring evenly, flotation is carried out. The floating foam is collected, the solid is filtered and washed with deionized water 3 times to obtain purified quartz sand. (3) Acid leaching and drying: Transfer the purified quartz sand to a container, add a mixed acid solution of 5 to 7 times the weight of the purified quartz sand, stir at 50 rpm for 2 to 4 hours, filter to obtain the solid, soak in sodium carbonate aqueous solution for 20 to 40 minutes, wash with deionized water, and then dry at 100 to 150℃ for 3 to 5 hours to obtain high-purity quartz sand. The preparation steps of the modified collector in step (2) are as follows: 6-12 parts of (2-aminoethyl)trimethylammonium chloride hydrochloride, 8-14 parts of pentaerythritol tetramine, and 30-50 parts of ethanol are mixed evenly, nitrogen gas is introduced, and 35-65 parts of bisphenol F diglycidyl ether-ethanol solution are added dropwise at a rate of 3 mL / min under stirring at 100 rpm at 20-30℃. After reacting for 30-40 h, the temperature is raised to 65-75℃, and the reaction is continued for 25-35 h. The mixture is then concentrated for 1-2 h under a vacuum of -0.1 to -0.08 MPa to obtain the modified collector; the concentration of bisphenol F diglycidyl ether in the bisphenol F diglycidyl ether-ethanol solution is 20 wt%; the flotation conditions are an aeration rate of 0.5-1.5 m³ / min. 3 / min, microwave frequency 1250~2150MHz, stirring speed 150~300rpm, flotation time 3~9min.
2. The purification process for high-purity quartz sand according to claim 1, characterized in that, The chloride salt mentioned in step (1) is any one of sodium chloride, ammonium chloride, and calcium chloride.
3. The purification process for high-purity quartz sand according to claim 1, characterized in that, The sieve mesh size in step (1) is 40~220 mesh.
4. The purification process for high-purity quartz sand according to claim 1, characterized in that, In step (2), the weight of the deionized water is 4 to 8 times the weight of the quartz sand, and the weight of the modified collector is 0.1 to 1.5% of the weight of the quartz sand.
5. The purification process for high-purity quartz sand according to claim 1, characterized in that, The mixed acid solution in step (3) is prepared by mixing 6wt% sulfuric acid, 2wt% hydrochloric acid and 10wt% oxalic acid in a volume ratio of 1:2:
1.
6. The purification process for high-purity quartz sand according to claim 1, characterized in that, The sodium carbonate content in the sodium carbonate aqueous solution in step (3) is 10 wt%.
7. The purification process for high-purity quartz sand according to claim 1, characterized in that, The pH of the washing solution after washing in step (3) is 6.5~7.5.
Citation Information
Patent Citations
Method for purifying quartz through microwave heating chloridizing roasting
CN114436266A
Microwave-conductance assisted flotation method and application thereof in quartz sand purification
CN120205338A
